Intra-tumoral sphingobacterium multivorum promotes triple-negative breast cancer progression by suppressing tumor immunosurveillance - Zhikai Mai; Liwu Fu; Jiyan Su; Kenneth K.W. To; Chuansheng Yang; Chenglai Xia (Molecular Cancer)
Abstract Background Intratumor-resident bacteria represent an integral component of the tumor microenvironment (TME). Microbial dysbiosis, which refers to an imbalance in the bacterial composition and bacterial metabolic activities, plays an important role in regulating breast cancer development and progression. However, the impact of specific intratumor-resident bacteria on tumor progression and their underlying mechanisms remain elusive. Methods 16S rDNA gene sequencing was used to analyze the cancerous and paracancerous tissues from breast cancer patients. The mouse models of bearing 4T1 cell tumors were employed to assess the influence of bacterial colonization on tumor growth. Tissue infiltration of regulatory T (Treg) cells and CD8+ T cells was evaluated through immunohistochemistry and flow cytometric analysis. Comparative metabolite profiling in mice tumors was conducted using targeted metabolomics. Differential genes of tumor cells stimulated by bacteria were analyzed by transcriptomics and validated by qPCR assay. Results We found that Sphingobacterium displayed high abundance in cancerous tissues. Intra-tumoral colonization of Sphingobacterium multivorum (S. multivorum) promoted tumor progression in 4T1 tumor-bearing mice. Moreover, S. multivorum diminished the therapeutic efficacy of αPD-1 mAb, which was associated with the increase of regulatory T cell (Treg) infiltration, and decrese of the CD8+ T cell infiltration. Targeted metabolomics revealed a conspicuous reduction of propionylcarnitine in tumors colonized by S. multivorum Furthermore, the combination of metabolite propionylcarnitine and S. multivorum shown to suppress tumor growth compared that in S. multivorum alone in vivo. Mechanistically, S. multivorum promoted the secretion of chemokines CCL20 and CXCL8 from tumor cells. CCL20 secreted into the TME facilitated the recruitment of Treg cells and reduced CD8+ T cell infiltration, thus promoting tumor immune escape. Conclusions This study reveals S. multivorum suppresses immune surveillance within the TME, thereby promoting breast cancer progression.